Genome-wide analysis of the laccase (LAC) gene family in Aeluropus littoralis: A focus on identification, evolution and expression patterns in response to abiotic stresses and ABA treatment - Hashemipetroudi, Seyyed Hamidreza; Arab, Mozhdeh; Heidari, Parviz; Kuhlmann, Markus (Frontiers in Plant Science, 2023)
Laccases play essential roles in plants in terms of growth and development, lignin polymerization, and responses to environmental stress. However, studies of laccases in some plants and fungi have highlighted that many structural and functional aspects of these genes are still unknown. In the current study, the laccase gene family in Aeluropus littoralis (AlLAC) was evaluated based on sequence structure and expression patterns under abiotic stresses and ABA treatment. Fifteen non-redundant AlLACs were identified from the A. littoralis genome, which showed differences in physicochemical characteristics and gene structure. Based on phylogenetic analysis, AlLACs and their orthologues were classified into five groups. A close evolutionary relationship was observed between LAC gene family members in rice and A. littoralis. According to the interaction network, AlLACs interact more with proteins involved in biological processes such as iron incorporation into the metallo-sulfur cluster, lignin catabolism, regulation of the symbiotic process, and plant-type primary cell wall biogenesis. Gene expression analysis of selected AlLACs using real-time qPCR revealed that AlLACs are induced in response to abiotic stresses such as cold, salt, and osmotic stress, as well as ABA treatment. Moreover, AlLACs showed differential expression patterns in shoot and root tissues. Our findings indicate that AlLACs are more involved in the late response of A. littoralis to abiotic stress.